Age-Inclusive ICT Innovation for Service Delivery in South Africa 2022
DOI: 10.1007/978-3-030-94606-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Older South Africans’ Cell Phone Use in Diverse Settings: A Baseline Assessment

Abstract: Interventions through Information and Communication Technology (ICT) (eInterventions), particularly cell phones, are increasingly regarded as feasible alternatives to address older individuals’ access to social and health care and services. Limited documented evidence of older South Africans’ cell phone use inhibits the full relevant operationalizing of eInterventions. This chapter sets out to present baseline evidence of a cohort of older persons’ cell phone use in South Africa. Two questionnaires, iGNiTe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For instance, studies have shown that up to 27% of the older urban population lacks Internet connectivity (UN-Habitat, 2021). In addition, the significant digital divide and, more spherically, the lack of digital skills and literacy among the elderly contributes to the digital exclusion of this population group (Bothma et al, 2022; Mubarak and Suomi, 2022). Consequently, they are excluded from basic services and social connections (Kanobe et al, 2022).…”
Section: Societal Impacts Of the Deployment Of Digital Technologies I...mentioning
confidence: 99%
“…For instance, studies have shown that up to 27% of the older urban population lacks Internet connectivity (UN-Habitat, 2021). In addition, the significant digital divide and, more spherically, the lack of digital skills and literacy among the elderly contributes to the digital exclusion of this population group (Bothma et al, 2022; Mubarak and Suomi, 2022). Consequently, they are excluded from basic services and social connections (Kanobe et al, 2022).…”
Section: Societal Impacts Of the Deployment Of Digital Technologies I...mentioning
confidence: 99%